Application of Fibonacci retracement in movement of stock market / Nur Farain Mohamed Fadzil, Nur Rabiatul Aisyah Rahmat Omar and Nabilah Othman - Mohamed Fadzil, Nur Farain; Rahmat Omar, Nur Rabiatul Aisyah; Othman, Nabilah (2022)
The stock market widely refers to the gathering of exchanges and different venues in which the buying, selling, and issuance of stocks of publicly-held organizations take place. Fibonacci retracement is a method used in this study to predict the price of the stock market. Fibonacci retracement is a very popular tool used by many technical traders to help identify strategic places for transactions to be placed, target prices or stop losses. There are several methods to analyze and predict the price of the stock market such as Genetic Algorithms and Network, but these methods are not as effective as Fibonacci Retracement due to inaccuracy and unable to predict stock market movement and price of the stock market in a long term. Hence, this study aims to analyze the movement of the stock market during COVID-19 and to measure the prediction on price of the stock market using Fibonacci Retracement method. This study focuses on the stock market in Bursa Malaysia specifically the health care sector. Three companies were chosen which are KPJ Healthcare Berhad, IHH Healthcare Berhad and Hartalega Holdings Berhad in Shariah Compliance. The result shows that Fibonacci retracement levels are an important component of technical analysis and should be included in investment strategy. Fibonacci retracements usage in the stock market does not make the traders or investors professional, but by using the Fibonacci retracement in conjunction with other technical analysis tools to predict entry and exit points in the stock market, the findings were proven to have a greater accuracy. This study also discover that Fibonacci Retracement method is very useful in every technical chart.